Time to move beyond monological perspectives in health behavior change communication research and practice - Schöps, Antje Maria; Skinner, Timothy Charles; Fosgerau, Christina Fogtmann (Frontiers in Psychology, 2023)
Chronic disease self-management and health behavior change programs are becoming increasingly important to health service delivery to prevent the development of chronic disease and optimize health outcomes for those who suffer from it. To train people to deliver these programs effectively, we need to understand both the what and how of program delivery. Whilst there is an abundant literature on what, and a merging evidence about what techniques to use, such as goals setting and self-monitoring, the literature on how programs should be delivered is less well developed. This paper reviews emerging research in this area and identifies an underlying monological approach. We argue that this currently dominant model cannot address the key issues in this area. By considering the theoretical framework of Dialogism, we introduce the method of Conversation Analysis to the field of behavior change interventions. Extensive research into health communication has endeavored to show the importance of language and the organization of interactions. We demonstrate and discuss how a monological approach to interventions prevents exploration of what professionals do to deliver intervention content. In doing so, we show that techniques do not account for how successfully an intervention is delivered.